2012
DOI: 10.1074/jbc.m111.330621
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Analysis of Cofactor-dependent Phosphoglycerate Mutase Homologs as Novel Phosphoserine Phosphatases in Hydrogenobacter thermophilus

Abstract: Background:The lack of a known phosphoserine phosphatase (PSP) gene has been a missing link in the serine biosynthetic pathway for a number of organisms. Results: Proteins with PSP activity were purified from a bacterium that lacks a classical-type PSP. Conclusion: Some cofactor-dependent phosphoglycerate mutase homologs function as novel-type PSPs. Significance: This finding will help to identify the missing link in the serine biosynthetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…The last enzyme PSP was initially identified by enzyme purification and protein identification via MS. However, the final recognition of the wrongly annotated Slr1124 as PSP was supported by the report on a new PSP class showing some sequence similarities to phosphoglycerate mutases (Chiba et al, 2012). Finally, using the three verified protein sequences from Synechocystis, we found homologous proteins in the majority of cyanobacterial genomes.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The last enzyme PSP was initially identified by enzyme purification and protein identification via MS. However, the final recognition of the wrongly annotated Slr1124 as PSP was supported by the report on a new PSP class showing some sequence similarities to phosphoglycerate mutases (Chiba et al, 2012). Finally, using the three verified protein sequences from Synechocystis, we found homologous proteins in the majority of cyanobacterial genomes.…”
Section: Discussionmentioning
confidence: 61%
“…It turned out that this putative phosphoglycerate mutase might be a promising PSP candidate. Chiba et al (2012) reported that a non-typical phosphoglycerate mutase of the bacterium Hydrogenobacter thermophilus displayed only PSP activity instead of the expected mutase activity. Hence, this enzyme was described as the first example for a new class of PSP enzymes, which have close relatives in many other organisms, including Arabidopsis.…”
Section: F Klemke and Othersmentioning
confidence: 99%
“…These kinetic constants were observed to be lower in comparison with those obtained for PSP enzymes characterized from either Hydrogenobacter thermophiles (K m of 1.6 mM), P. gingivalis (K m of 2.0 mM and 2.6 mM for phosphoserine peptides), or Pseudomonas aeruginosa (K m of 207 M) (26,36,37). We also observed that maximal SerB2 activity was observed in the initial 5 min and that inclusion of 0.01% Triton X-100 enhanced SerB2 activity by 15-20% (Fig.…”
mentioning
confidence: 60%
“…L-O-phosphoserine ϩ H 2 O 3 L-serine ϩ phosphate), were recently identified and characterized from Hydrogenobacter thermophilus TK-6, an obligately chemolithoautotrophic, thermophilic bacterium belonging to the order Aquificales (1)(2)(3). Although the kinetic parameters of iPSPs for L-phosphoserine are similar to those of conventional Mg 2ϩ -dependent phosphoserine phosphatases (dPSPs), iPSPs do not require divalent cations for their activity.…”
mentioning
confidence: 99%
“…In addition, the five catalytic core residues (four conserved residues and an additional aspartate/glutamate) that are characteristic of the histidine phosphatase superfamily are completely conserved in both iPSP subunits and dPGMs. For this reason, iPSPs were originally annotated as dPGMs; however, iPSPs lack the residues proposed to be important for mutase activity and show no phosphoglycerate mutase activity (1,7,8). As iPSPs exhibit substantial phosphatase activity specific to L-phosphoserine, these enzymes are now thought to function as PSPs in vivo.…”
mentioning
confidence: 99%